2008
DOI: 10.1093/ije/dyn214
|View full text |Cite
|
Sign up to set email alerts
|

Social disparities in BMI trajectories across adulthood by gender, race/ethnicity and lifetime socio-economic position: 1986–2004

Abstract: Results highlight the importance of social status and socio-economic resources for maintaining optimal weight. Yet, even those in advantaged social positions have experienced an increase in BMI in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
193
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 52 publications
(63 reference statements)
14
193
5
Order By: Relevance
“…For each strata, they showed that weight gain was most rapid for those in their 20s, 30s, and 40s and then tended to level off and then decrease after age 60 (7). However, neither they nor more recent growth curve or trajectory analyses by Clarke et al (4) or Østbye et al (6) provide separate estimates of likely weight trajectories by starting BMI category.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For each strata, they showed that weight gain was most rapid for those in their 20s, 30s, and 40s and then tended to level off and then decrease after age 60 (7). However, neither they nor more recent growth curve or trajectory analyses by Clarke et al (4) or Østbye et al (6) provide separate estimates of likely weight trajectories by starting BMI category.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have estimated average weight gain among adults in the general population or for specific population subsets (4)(5)(6)(7). For example, in a recent and highly cited study, Mozaffarian et al (5) reported average annual weight gain of 0.38 kg (0.84 lb) among nonobese adults in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Clarke et al, 2009;Reiter et al, 2009;Stegmueller, 2014;Tawfik et al, 2012), Bell and Jones (2013a, 2013b, 2014a questioned the validity of this approach. They asserted that it is impossible to assess the net effects of time-related changes accurately, without making the assumption that at least one of the age-period-cohort effects is equal to zero.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term trajectory of BMI over adulthood shows a largely linear increase with age for both men and women (Botoseneanu and Liang 2011), although weight gain appears to slow with age (He and Baker 2004). The well-documented secular increase in obesity prevalence is reflected in longitudinal studies; the BMI trajectories of younger cohorts are steeper than those of the older cohorts examined (Clarke et al 2009). …”
Section: Military Service and Body Weightmentioning
confidence: 99%
“…Most studies indicate that women have higher rates of weight gain with age than men (Clarke et al 2009;He and Baker 2004;Mujahid et al 2005;Walsemann and Ailshire 2011), although some find no gender difference (Botoseneanu and Liang 2011). Race is related to BMI trajectories, but its effects vary by gender.…”
Section: Military Service and Body Weightmentioning
confidence: 99%